One less monotypic genus in Leptophlebiidae (Ephemeroptera): A new species of Bessierus Thomas & Orth and new record from Brazil - Cruz, Paulo Vilela; Gonçalves, Inês C.; Mariano, Rodolfo; Hamada, Neusa (Zootaxa, 2020)
A new species of Bessierus Thomas & Orth, formerly a monotypic genus, is described from Amapá State, Brazil. The type species of the genus, B. doloris Thomas & Orth, had only its nymphs described until recently, when its male imago was associated to nymphs mainly based on pigmentation pattern. Bessierus riobranco sp. n. here described has no significant difference on pigmentation pattern from B. doloris, thus the new species could be the male imago of B. doloris, and the putative imago of B. doloris a new species, or even both described imagoes could be new species. Still, a new male imago existence cannot be neglected and we opted to provide a properly description, diagnosis and illustration, hence contributing to the knowledge of mayfly neotropical diversity and future research on the genus. The generic concept of Bessierus and its type species diagnoses are altered to accommodate the new species, and a new record of B. doloris is provided.